The Effect Of Top Down And Bottom Up Strategies To Improve Listening Skill At Tenth Grade Students Of Sma Dwijendra Bualu - Dunga, Asriati Ina; Kurniawati, Kadek Lina; Sintadewi, Ni Made Dita (Peneliti.net, 2025)
This study aims to determine the effect of Top Down and Bottom Up strategies on improving listening skills at tenth grade students of SMA Dwijendra Bualu High. The sample in this study consisted of 26 tenth grade students selected through purposive sampling and this study employed a pre-experimental design with a single-group pre-test and post-test method to collect data, using a quantitative approach. The measurement tools used were a listening comprehension test in the form of fill-in-the-blank questions and a questionnaire as supporting data to determine students perceptions. The data collected were examined using descriptive and inferential statistical analyses using SPSS version 25. The results of the study showed a significant improvement in students listening skills after the implementation of the Top Down and Bottom Up strategies. The students total scores increased from 1546 (pre-test) to 2071 (post-test). The difference in average scores was -20.192, with a Sig. value of 0.000, indicating that the difference was statistically significant (p < 0.05). Additionally, the questionnaire results showed that students had a positive perception of the use of both strategies. The average perception scores ranged from 4.00 to 4.35, falling into the ‘Agree’ to ‘Strongly Agree’ category on the 1-5 Likert scale. This indicates that the Top-Down and Bottom-Up strategies were well-received by students and considered effective to highly effective. Therefore, it can be concluded that the Top Down and Bottom Up strategies are effective in improving listening skills.